Two-step dependence modelling via copula functions for insurance risks - Borges, André Nunes (2023)
Risk management is of great importance for insurance companies, not only for uncertainty being at the core of the business, but due to compliance with regulatory hallmarks such as the Basel Accords. The use of copulas for modelling dependence between random variables in a top-down manner has grown in the past decade due to its flexibility. In this work, copulas are used to access the dependence between premium and claims in order to construct a loss-ratio distribution and Vine Copulas are used to access the dependence between loss-ratios of different risk lines, in a two-step fashion.